REDOTHERM: a thermodynamic modeling framework for redox-based thermochemical processes - Lidor, Alon; Martinek, Janna (Frontiers in Energy Research, 2025)
Two-step thermochemical redox cycles are being developed as a potential pathway for the production of hydrogen and syngas. While there are many possible reactor and system configurations, moving oxide systems are considered promising in terms of the redox thermodynamics, due to the potential implementation of a countercurrent system that can achieve higher performance compared to other configurations. There is a lack of a robust thermodynamic modeling framework in the field, with multiple models incorporating incorrect thermodynamic assumptions that violate the second law of thermodynamics. We present in this work REDOTHERM, an open-source system model for moving oxides that incorporates the correct thermodynamic limits, as well as various options for the system auxiliary units including product separation, heat recovery, and oxygen removal. The model is agnostic to the energy source, and could be used for solar thermal or other configurations. We highlight the uses of this model, presenting some of the tradeoffs and challenges in redox-active material selection and how they affect the entire thermochemical hydrogen production process. This model could be easily adapted and used for material exploration, system/reactor design, and technoeconomic analysis.